Perioperative management of anticoagulant therapy - Wagner, Johanna (Innov Surg Sci, 2019)
About 10% of patients taking a chronic, oral anticoagulant therapy require an invasive procedure that can be associated with an increased risk for peri-interventional or perioperative bleeding. Depending on the risk for thromboembolism and the risk for bleeding, the physician has to decide whether the anticoagulant therapy should be interrupted or continued. Patient characteristics such as age, renal function and drug interactions must be considered. The perioperative handling of the oral anticoagulant therapy differs according to the periprocedural bleeding risk. Patients requiring a procedure with a minor risk for bleeding do not need to pause their anticoagulant therapy. For procedures with an increased risk for perioperative bleeding, the anticoagulant therapy should be adequately paused. For patients on a coumarin derivative with a high risk for a thromboembolic event, a perioperative bridging therapy with a low molecular weight heparin is recommended. Due to an increased risk for perioperative bleeding in patients on a bridging therapy, it is not recommended in patients with a low risk for thromboembolism. For patients taking a non-vitamin K oral anticoagulant, a bridging therapy is not recommended due to the fast onset and offset of the medication.